Dual tongue: the unexpected origin - Naserrudin, Nadia Syafeera; Ainer, Indumathi; Doi, Mohamad; Liew, Kong Yew; Abu Bakar, Saraiza (Public Opinion Times, 2018)
Laryngeal lipoma is a very rare benign laryngeal tumour. Although it has an indolent growth, laryngeal lipoma can lead to compression and obstruction at upper aero digestive tract which leads to dysphagia, dyspnoea and hoarseness. Case Report: A 26-year-old man who came with presenting complaint that he developed a second tongue recently. His voice has turned muffled. Examination showed an accessory tongue appeared to arise from supraglottic region from nasoendoscopy. A transoral endoscopic excision of the lipoma was done. He has a complete resolution of symptom immediately following surgery with no recurrence on follow up. Conclusion: A complete excision of laryngeal lipoma is important as its location may cause mechanical narrowing of upper aerodigestive tract, giving symptoms of airway obstruction and difficulty swallowing. We highlighted the structures that may involve in laryngeal lipoma and its type.